Investigation of the friction reduction and anisotropy of seta structure with large deflection cantilever beam model. (August 2022) - Cheng, Qian; Yang, Fan; Jiang, Han; Cai, Hongbin
Abstract: Most insects can regulate friction with their seta structure when moving or crawling. To investigate the complicated friction behavior brought by the large deflection of seta structure, the nonlinear cantilever beam model with reactive support and friction force was established. The friction experiments of the seta structure were also conducted to verify the analytical results. The effect of loading conditions on the friction behavior of seta structure was discussed. It demonstrates that the friction force reacts nonlinearly with the applied normal displacement and exhibits obvious friction-reduction. The seta structure exhibits frictional anisotropy when sliding forward or backward which becomes more pronounced for small applied displacement and initial angle. Those findings provide valuable insights into the insects' tribology mechanisms. Highlights: The nonlinear large deflection cantilever beam model with reactive support and friction force was established. The nonlinear large deflection of seta structure results in the rapid descent of the increment of reactive friction force. The structure's nominal friction coefficient is no longer linearly equivalent to material's friction coefficient. The friction anisotropy is more pronounced for small applied displacement and initial angle.